Integrating models of long-term athletic development to maximize the physical development of youth - Pichardo, A. W.; Oliver, J. L.; Harrison, C. B.; Maulder, P. S.; Lloyd, R. S. (International Journal of Sports Science & Coaching, 2018)
Long-term athletic development is important to prepare youth for sport and an active lifestyle. Several models have provided general frameworks for long-term athletic development from different perspectives that consider factors such as when to sample and specialize and what physical qualities to train and when. More recently, more specific models of long-term athletic development have emerged that focus on both specific modes of training and specific fitness qualities. This includes models focused on the development of speed, agility, power, and endurance as well as models devoted to resistance training, plyometric training, and weightlifting. These models incorporate factors such as technical competency, developmental stage, maturation, and training age to describe the long-term progression of athletic development. A challenge for the coach is to understand how these models inform one another and how they integrate into practice to allow the use of multiple modes of training to develop multiple components of fitness simultaneously throughout childhood and adolescence. This review will examine how information from various models can be integrated to maximize the physical long-term athletic development of youth.